(untitled) (Pursuits: A Journal of English Studies, 2025)
This paper explores the plight of Tamil Refugees who are trapped to depart their ancestral land and suffer a humanitarian crisis through an analysis of Sharon Bala’s The Boat People. Tamil refugees have been living horrendously displaced lives from the early 1980s to the present in different parts of the world, particularly in Canada. This study uncovers the Tamil refugee humanitarian catastrophe to sustain their lives, resulting in a stateless population after being excluded from their inherited Land in Sri Lanka as a consequence of ethnic conflict. So, this paper adopts the theoretical frameworks of Giorgio Agamben, Hannah Arendt, and Thomas Nail to reflect the precarious situation of Tamil Refugees. Additionally, it embraces John Locke, Richard and Zapata Barrero to address this issue and the plight of Tamil Refugees. This paper concludes that Tamil immigrants are extremely dehumanized by portraying the obvious evidence of the protagonist Mahindan, who is intertwined in the perplexing legal process of Canada. Similarly, Tamil refugees are under a severe humanitarian crisis, thrown into such a situation to fight against the necessities of life, such as a lack of food, unsafe drinking water, insecure shelter, and harmful insects. While travelling, they have to take the risk of a life-threatening perilous journey on a wrecked boat and again inhuman imprisonment inside detention centres, to mistreatment after landing in Canada. Thus, they are in anxiety, frustration, pain, and misery, being excluded from the political sphere in both the Native and host countries.